Avaliação de diferentes técnicas cirúrgicas na abordagem da hemorragia pós-parto com e sem preservação uterina - Alvaro Luiz Lage Alves (2018)
Introduction: postpartum haemorrhage is the largest worldwide cause of peripartum hysterectomy, even among women with a desire for future fertility. In Brazil, hemorrhage continues to be among the three main groups of causes of death in the pregnancy-puerperal cycle. This study evaluated different surgical techniques with and without uterine preservation in the treatment of postpartum haemorrhage. Methods: a retrospective analysis of uterine preservation surgical techniques used in patients who evolved postpartum haemorrhage between 2014 and 2017 at the Hospital Sofia Feldman, in the city of Belo Horizonte, Brazil, was performed. The choice of surgical techniques was defined by institutional protocol and professional experience and skill. The study documented and compared the various groups of surgical techniques adopted in postpartum haemorrhage, with and without uterine preservation, and evaluated two new techniques: the Alves handcrafted intrauterine balloon and the Barbosa da Silva technique, which combines uterine devascularization and suture uterine compression. Results: out of a total of 484 patients, 130 underwent a surgical technique, including vascular ligatures, compressive uterine sutures, intrauterine balloons, hysterectomies and segmental myometrial excision with reconstruction of the uterine wall. There were no statistically significant differences between the techniques in terms of efficiency in achieving hemorrhagic control. Intrauterine balloons were associated with high blood transfusion rates. The Alves handcrafted intrauterine balloon was efficient for uterine tamponade and was also useful in the treatment of bleeding from vaginal trauma. Vascular ligations were not associated with the need for intensive treatment. Besides the success in hemorrhagic control, the Barbosa da Silva technique presented versatility in the treatment of several etiologies and low rates of postoperative complications. Hysterectomies were primarily performed as the first line of surgical treatment of severely invasive placentas and were associated with high percentages of vasoactive amines, hemotransfusion, hypovolemic shock, intensive treatment and postoperative complications. Conclusions: the surgical techniques of uterine preservation presented satisfactory and similar results and should be considered in the surgical treatment of postpartum haemorrhage before hysterectomy. The professional's experience and ability and the way of delivery are important for the choice of techniques. Alves' artisanal intrauterine balloon and the Barbosa da Silva technique also showed efficacy in hemorrhagic control and uterine preservation, revealing themselves as new options for these purposes.